2018
DOI: 10.1097/md.0000000000009540
|View full text |Cite
|
Sign up to set email alerts
|

Noncystoscopic removal of retained ureteral stents in children

Abstract: Cystoscopic technique is the current common method of retrieving double J ureteral stent in most pediatric urological centers. In this study, we evaluated the feasibility and efficacy of a novel noncystoscopic method to remove retained ureteral stents in pediatric patients.We reviewed all medical records from a total of 102 patients who were treated in our hospital between January 2013 and December 2016 to remove the double J ureteral stent retained into the ureter. The pediatric patients were divided into 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…utilized the suture attached to a feeding tube (Vellore Catheter Snare) 23 . Similar results were observed in the non‐cystoscopic attempt of stent removal using a Lasso technique with success in boys and girls (97 and 41, respectively), 24 and again in 45 of 47 children 25 . The advent of blind ureteral stent removal has also been performed using a three‐way urethral catheter snare created from a looped guidewire 26 …”
Section: Discussionmentioning
confidence: 70%
“…utilized the suture attached to a feeding tube (Vellore Catheter Snare) 23 . Similar results were observed in the non‐cystoscopic attempt of stent removal using a Lasso technique with success in boys and girls (97 and 41, respectively), 24 and again in 45 of 47 children 25 . The advent of blind ureteral stent removal has also been performed using a three‐way urethral catheter snare created from a looped guidewire 26 …”
Section: Discussionmentioning
confidence: 70%
“…In this study, we reported a non-cystoscopic technique for double-J tube removal with a simple device of only a suture and one catheter. Our method has been reported in previous literature, such as the Vellore Catheter Snare technique ( 7 ) along with two similar techniques reported by Lin et al ( 8 ) and Shao et al ( 9 ). These studies have revealed that non-cystoscopic double-J tube removal had a shorter operation time and lower cost compared to that of a cystoscopic approach ( 7 9 ).…”
Section: Introductionmentioning
confidence: 64%
“…Our method has been reported in previous literature, such as the Vellore Catheter Snare technique ( 7 ) along with two similar techniques reported by Lin et al ( 8 ) and Shao et al ( 9 ). These studies have revealed that non-cystoscopic double-J tube removal had a shorter operation time and lower cost compared to that of a cystoscopic approach ( 7 9 ). However, these studies were performed with small sample size.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations